Cumulate xenoliths from Mt. Overlord, northern Victoria Land, Antarctica: A window into high pressure storage and differentiation of mantle-derived basalts - PERINELLI, CRISTINA; ARMIENTI, PIETRO; Gaeta, Mario (Lithos, 2017)
The alkaline basaltic magmas at Mt. Overlord (northern Victoria Land, Antarctica) entrained abundant ultramafic xenoliths (wehrlites, clinopyroxenites and hornblendites). Textures, bulk rock compositions, mineral chemistry and thermobarometric calculations indicate that the xenoliths represent cumulates that crystallised at the mantle–crust boundary. In particular, the major and trace element compositions of the bulk rocks and minerals indicate that the Mt. Overlord cumulates were formed through processes of crystal fractionation that affected hydrous basanitic magmas. Some of the xenoliths have textural features that suggest a lengthy (> 13 Myr) post-emplacement history at relatively low temperatures (1050–1100 °C) and high pressures (0.8 to 1.4 GPa) and that their primary parental melts were therefore related to the earliest phases of Cenozoic magmatism. These processes produced a “wet and hot deep zone” that had a strong influence on the thermochemical evolution of the lower crust beneath Mt. Overlord.